2022
DOI: 10.1093/ajcn/nqab308
|View full text |Cite
|
Sign up to set email alerts
|

Diet and food type affect urinary pesticide residue excretion profiles in healthy individuals: results of a randomized controlled dietary intervention trial

Abstract: Background Observational studies have linked pesticide exposure to various diseases, whereas organic food consumption has been associated with positive health outcomes. Organic farming standards prohibit the use of most pesticides, and organic food consumption may therefore reduce pesticide exposure. Objectives To determine the effects of diet (Western compared with Mediterranean) and food type (conventional compared with org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 45 publications
3
59
1
Order By: Relevance
“…Specifically, conventional fruits were found to have substantially higher pesticide loads than conventional vegetables and cereal-based foods, whereas contamination levels were similar in organic fruits, vegetables and cereal-based foods, but substantially lower than in their conventional comparators (Figure 7a). Similar results were obtained in recent retail surveys of fruits, vegetables and cereal-based foods [141], which reported that the number of different pesticide residues detected was substantially higher in conventional products, compared with organic fruit, vegetables and cereal-based food products (Figure 7b). A large retail survey of wheat flour products carried out over 3 years in the UK and Germany reported significant effects of wheat species (Triticum aestivum L. vs. T. spelta L. flour) and refining (white versus whole-grain flour) and the country in which flour samples were collected (the UK versus Germany), on pesticide residue concentrations in conventional, but not organic wheat flour, which generally contained very low pesticide residues [140] (Figure 8).…”
Section: Synthetic Chemical Pesticides That Are Prohibited In Organic Farmingsupporting
confidence: 89%
See 4 more Smart Citations
“…Specifically, conventional fruits were found to have substantially higher pesticide loads than conventional vegetables and cereal-based foods, whereas contamination levels were similar in organic fruits, vegetables and cereal-based foods, but substantially lower than in their conventional comparators (Figure 7a). Similar results were obtained in recent retail surveys of fruits, vegetables and cereal-based foods [141], which reported that the number of different pesticide residues detected was substantially higher in conventional products, compared with organic fruit, vegetables and cereal-based food products (Figure 7b). A large retail survey of wheat flour products carried out over 3 years in the UK and Germany reported significant effects of wheat species (Triticum aestivum L. vs. T. spelta L. flour) and refining (white versus whole-grain flour) and the country in which flour samples were collected (the UK versus Germany), on pesticide residue concentrations in conventional, but not organic wheat flour, which generally contained very low pesticide residues [140] (Figure 8).…”
Section: Synthetic Chemical Pesticides That Are Prohibited In Organic Farmingsupporting
confidence: 89%
“…Several dietary intervention studies with humans and some human cohort studies have assessed the effect of organic versus conventional food consumption on urinary excretion of pesticide residues, but there is limited data on urinary excretion of other health relevant compounds (e.g., phenolics, other phytochemicals, antioxidants and mineral micronutrients). These studies have consistently shown that organic food consumption results in significantly lower exposure to a range of pesticides, but identified no or only very small effects on the urinary excretion of other health relevant compounds [141,168,169,[185][186][187][188][189][190]; this evidence has been described and discussed in detail in a recent systematic review by Vigar et al [169].…”
Section: Evidence From Human Dietary Intervention and Cohort Studiesmentioning
confidence: 95%
See 3 more Smart Citations